Significance of wine and resveratrol in cardiovascular disease: French paradox revisited - Vidavalur, Ramesh (Pulsus Group Inc, 2006)
Many recent studies have reported promising health benefits from red wine consumption. The present article reviews some of the key studies, and the known mechanisms for these beneficial effects. Evidence from different experimental studies, including from the authors’ laboratories, have suggested that these beneficial effects are due to polyphenols found in red wine, especially resveratrol in grape skins. These benefits include a reduction in cardiovascular morbidity and mortality, lung cancer and prostate cancer by approximately 30% to 50%, 57% and 50%, respectively. Polyphenols possess antioxidant, superoxide-scavenging, ischemic-preconditioning and angiogenic properties. Some of these properties of polyphenols may explain their protective effects on the cardiovascular system, as well as other body organs. In fact, results from several epidemiological, case-control and prospective studies have prompted the United States Department of Health and Human Services to recommend moderate alcohol consumption in its national health promotion and disease prevention initiative, Healthy People 2010. Further studies are warranted to describe the precise molecular mechanisms for these potential beneficial effects of red wine on the general health of the population, particularly on cardiovascular morbidity and mortality.